Jargon Used by Traditional Cockfighting Ceremony At Cempaga Village - Kurniawan, Mas Adi; ramendra, Dewa Putu; Juniarta, Adi Krisna (Jurnal Pendidikan Multikultural Indonesia, 2021)
This research was designed by descriptive qualitative study. This study aims to find the jargon that exists in the traditional cockfighting ceremony. This research took place in the subak temple in Cempaga village. Observations and interviews are used to obtain the data in this research.Â  Interviews were conducted by interviewing two trusted informants. The results show that there are 43 jargons found in this traditional cockfighting ceremony. The jargon can be divided into 2 types. Some are included in the word formation process and word class. 25 word classes, 12 affixations and 6 compounding words. All jargons have their own meanings that will be used by the players (bobotoh) in the cockfighting arena.